Vertical Integration on Russian Metallurgical Market: Preconditions and Consequences - E. A. Braiko (Вестник Российского экономического университета имени Г. В. Плеханова, 2025)
The article analyzes the process of building metallurgical industry in Russia, key landmarks of its formation, which led to its current standing as vertically integrated companies. Key trends of integration were studied – forward and backward, it was explained in what periods of development these vectors were chosen and why. The author gave examples of both positive and negative experience of vertical integration illustrating it by leading Russian metallurgical companies. Apart from that, risks were shown which faced top-management of companies that made a decision about vertical integration. The author described changes that took place on Russian metallurgical market in the time of global economy turbulence in 2020–2023 and gave practical recommendations aimed at overcoming difficulties. The hypothesis was corroborated that structure of Russian metallurgical market as vertically integrated companies proved its stability and adaptive capacity in conditions of fast changing market situation.